Determinants of Local Currency Bonds and Foreign Holdings: Implications for Bond Market Development in the People's Republic of China - Kee-Hong Bae (Asian Development Bank (ADB), 2012)
This case study explores which variables—macroeconomic, institutional, and capital controls—are most important in explaining cross-country differences in bond market development. It uses the ratio of amount of local currency bonds outstanding over GDP as a measure of bond market development from 43 countries during 1990–2009. The study examines government and corporate bond markets separately, as the characteristics of these markets are substantially different and requires separate examination. > Main findings are derived from the comparative analysis. Several policy implications drawn from the findings are pertinent to the People`s Republic of China (PRC) bond market. The most important implication is that the way to develop fixed income markets is to start with the government bond market. Another important implication from the empirical findings is that mature and well-developed banking sector is critically important to the further development of bond market, particularly to the corporate bond market. While the PRC bond market has developed significantly over recent years, there is much room for improvement. This report provides policy suggestions, albeit not necessarily from empirical findings, to further develop PRC bond markets.
hdl:11540/1304
Keywords: E63; E65; G14; G18; G24; G28; N20; 330; PRC bond market; debt securities; determinants; regulatory and legal infrastructure; off-shore CNY bonds; Internationale Anleihe; Finanzmarktregulierung; Rentenmarkt; China